When I Say…Human. Issue 9 (21st April 2021) - MacLeod, Anna; Luong, Victoria; Cameron, Paula; Kovacs, George; Patrick, Lucy; Tummons, Jonathan; Kits, Olga
Abstract : What makes us human? Is it a question that matters? Luong et al. explore these questions in the latest instalment of "When I Say…"